2023
DOI: 10.3390/jcm12062368
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Characteristics in Acute and Resolved Vogt-Koyanagi-Harada Disease

Abstract: Vogt-Koyanagi-Harada (VKH) disease is an auto-immune inflammatory disease of choroidal origin. During the acute stage, optical coherence tomography (OCT), however, may not be able to assess the entire choroid. The aims of the paper were to evaluate the role of retinal pigment epithelium (RPE) as a biomarker of inflammation in acute VKH. This was a retrospective observational study done in 55 eyes of 29 patients with acute VKH. RPE thickness, total choroidal thickness, and RPE reflectivity before and after reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Jacob et al previously tried to evaluate the RPE reflectivity in eyes with VKH disease and reported an increase in RPE reflectivity during the resolution of VKH, 32 which differed from the results presented in our manuscript. The differences in our findings can be attributed to several factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Jacob et al previously tried to evaluate the RPE reflectivity in eyes with VKH disease and reported an increase in RPE reflectivity during the resolution of VKH, 32 which differed from the results presented in our manuscript. The differences in our findings can be attributed to several factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Such a procedure has already been used and validated. 13,14 Using this software, we measured two parameters at the level of these territories: the vessels percentage area and the average vessels length. We compared these values with those of a territory of the same mirrored surface about the horizontal meridian.…”
Section: Optical Coherence Tomography Analysismentioning
confidence: 99%
“…[ 4 , 5 ] The retinal pigment epithelium (RPE) is a monolayer of pigment cells that is involved in the pathological process of VKH disease. [ 6 , 7 , 8 , 9 ] Long‐held theories suggest that the symptoms of VKH disease may be caused by an autoimmune response to melanin. [ 4 , 7 ] In the early stage of VKH disease, human melanoma cells are severely affected by T cells, presenting as folds of RPE.…”
Section: Introductionmentioning
confidence: 99%